2009
DOI: 10.4310/ajm.2009.v13.n1.a3
|View full text |Cite
|
Sign up to set email alerts
|

Bäcklund Transformations and Darboux Integrability for Nonlinear Wave Equations

Abstract: Abstract. We prove that second-order Monge-Ampère equations for one function of two variables are connected to the wave equation by a Bäcklund transformation if and only if they are integrable by the method of Darboux at second order.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…5.2) giving an EDSĪ 2 on a five manifold. The EDSĪ 2 is not a Pfaffian system but is known as a Monge-Ampére system [7]. In this case diagram (2.2) can be refined.…”
Section: Summary Of Results For Hyperbolic Pde In the Planementioning
confidence: 98%
See 2 more Smart Citations
“…5.2) giving an EDSĪ 2 on a five manifold. The EDSĪ 2 is not a Pfaffian system but is known as a Monge-Ampére system [7]. In this case diagram (2.2) can be refined.…”
Section: Summary Of Results For Hyperbolic Pde In the Planementioning
confidence: 98%
“…In [2] it is shown that if F = 0 is Darboux integrable (without prolongation) and admits a Bäcklund transformation to the wave equation z xy = 0 (with one-dimensional fibres as in [7]), then the Bäcklund transformation can be constructed by group reduction using Theorem 1. In order to describe these results formally let I 2 be the standard rank 3 hyperbolic Pfaffian system determined by the restriction of the contact system on J 2 (R 2 , R) [9] to the level set M in (2.1).…”
Section: Summary Of Results For Hyperbolic Pde In the Planementioning
confidence: 99%
See 1 more Smart Citation
“…If locally either V 3 or W 3 is zero, which is independent of the choice of 1-refined liftings, the underlying Bäcklund transformation must relate a hyperbolic Euler-Lagrange system with the system corresponding to z xy " 0. See [CI09] and [Zvy91] for a classification of all hyperbolic Monge-Ampère systems that are rank-1 Bäcklund-related to the equation z xy " 0.…”
Section: Type Iia In This Case (19) Implies Thatmentioning
confidence: 99%
“…In addition to the elliptic and hyperbolic examples mentioned above, a Bäcklund transformation may exist relating solutions of a parabolic equation (see [NC82]) or an equation of order higher than 2, for example, the KdV equation (see [WE73]). Furthermore, two PDE systems being Bäcklund-related need not be contact equivalent to each other (see [CI09]).…”
Section: Introductionmentioning
confidence: 99%